2020
DOI: 10.3390/plants9060763
|View full text |Cite
|
Sign up to set email alerts
|

More than Scales: Evidence for the Production and Exudation of Mucilage by the Peltate Trichomes of Tillandsia cyanea (Bromeliaceae: Tillandsioideae)

Abstract: Bromeliad scales have been investigated extensively due to their recognition as a key ecological and evolutionary feature of Bromeliaceae. However, much remains unknown about such trichomes and only recently mucilage exudation was described for them in a species of the subfamily Bromelioideae. The present study aimed to investigate the secretion present in inflorescences of Tillandsia cyanea Linden ex K. Koch (Tillandsioideae) to determine whether the scales of this species also produce and release secretions.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 72 publications
(125 reference statements)
1
9
0
1
Order By: Relevance
“…Nevertheless, the positive reaction of the ruthenium red test showed that the calycinal glands of R. ornata likely contain mucilaginous and hygroscopic substances, as was also found in Ipomoea cairica (L.) Sweet [ 26 ], and were defined as colleters (any of the morphologically diverse secretory organs functioning homologously in secreting mucilaginous or resinous fluids [ 13 ]). Based on the properties of the secreted substances, calycinal glands are believed to protect flower buds, from their development until fruiting, from desiccation and insolation [ 26 , 58 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, the positive reaction of the ruthenium red test showed that the calycinal glands of R. ornata likely contain mucilaginous and hygroscopic substances, as was also found in Ipomoea cairica (L.) Sweet [ 26 ], and were defined as colleters (any of the morphologically diverse secretory organs functioning homologously in secreting mucilaginous or resinous fluids [ 13 ]). Based on the properties of the secreted substances, calycinal glands are believed to protect flower buds, from their development until fruiting, from desiccation and insolation [ 26 , 58 , 107 ].…”
Section: Discussionmentioning
confidence: 99%
“…and reported differences in terms of floral tube, anther, and stigma length. Ballego-Campos et al (2020) predicted that dense secretion based on the presence of trichomes in the flower parts of Tillandsia cyanea Linden ex K. Koch (Bromeliaceae) contributes to the development of flower buds and the preservation of the delicate corolla structure. In this study, the hairs on the outer surface of the corolla tube and the corolla lobes may have taken on the task of protecting the sensitive corolla.…”
Section: Discussionmentioning
confidence: 99%
“…The leaves of bromeliads are commonly covered with specialized peltate trichomes capable of absorbing water and nutrients that, in some cases, can replace the absorptive function of the roots (Benzing, 2000). The presence and density of these trichomes on leaf blades might reflect different adaptations to water and nutrient intake (Givnish et al, 1984; Martin, 1994; Benz & Martin, 2006), as well as other functions, like light reflectance and secretion of mucilage (Benzing et al, 1985; Benzing, 2000; Ballego‐Campos et al, 2020). To capture this variation, we coded this trait as glabrous to glabrescent (state 0) and clearly covered with peltate scales on either side of the blade (state 1).…”
Section: Methodsmentioning
confidence: 99%